Kohezivni vzorec matematičnih besedil - Gorjanc, Vojko (Slavistična revija, 1999)
With respect to the typology of cohesive ties presented in the article, the author analyzes teh formation of patterns of cohesion in Slovene mathematical texts. As the text progresses, the distance between the two components of the cohesive tie increases; for the reception of the text this distance is relevant particulary in the framework of coreference. Another aspect of observing cohesive pattern is discussed as a special text-building element.
Keywords: matematika; slovenščina; tekstna lingvistika